Influence of the relative age effect on children’s scores obtained from the Canadian assessment of physical literacy - Caroline Dutil (BMC Public Health, 2018)
Abstract Background Age grouping by the imposition of a cut-off date, common in sports and education, promotes a relative age difference that is associated with developmental advantages for children who are born on the “early side” of the cut-off date and disadvantages to those born later in the same year, which is known as the relative age effect (RAE) bias. Acquiring an adequate level of physical literacy is important for children to remain active for life. The Canadian Assessment of Physical Literacy (CAPL) is an assessment protocol that encompasses measures in the domains of children’s Daily Behaviours, Physical Competence, Motivation and Confidence, and Knowledge and Understanding. The purpose of this study was to ascertain whether the CAPL scores were susceptible to the RAE, which could affect our interpretation of the CAPL findings. Methods This cross-sectional study examined if scores obtained in the CAPL (i.e., the four domains individually and the total CAPL score) were susceptible to the RAE in children aged 8 to 12 years and, if so, which physical competence assessments (movement skills, cardiorespiratory, strength, muscular endurance, flexibility, and body composition measurements) were more susceptible. Participants (n = 8233, 49.8% boys) from the Royal Bank of Canada–CAPL Learn to Play project from 11 sites in seven Canadian provinces were tested using the CAPL protocol. Results Among boys and girls, the RAE was significantly associated with two and three of the four domain scores, respectively, after controlling for covariates. However, effect sizes were negligible for the comparisons between quarters of the year and physical literacy domains and overall scores. For the main effect of the relative age, boys and girls born in the first three months of the year were taller (F(3, 4074) = 57.0, p < 0.001, ƒ2 = 0.04 and F(3, 4107) = 58.4, p < 0.001, ƒ2 = 0.04, respectively) and demonstrated greater muscular strength (F(3, 4037) = 29.2, p < 0.001, ƒ2 = 0.02 and F(3, 4077) = 25.1, p < 0.001, ƒ2 = 0.02, respectively) compared with those born later in the same year. Conclusions Collectively, our results suggest that the RAE bias is mainly negligible with regard to the domain scores and overall CAPL scores in this large sample of children.